Relationship of psychosocial safety climate and workplace psychosocial risks: a randomized trail among personnel of an oil and gas company in Iran - Amiri, Dordaneh; Sann, Lye Munn; Adon, Mohd Yusoff; Mukhtar, Firdaus; Idris, Khairuddin; Kuhn, Karl; Kamari, Ali Abbas (Canadian Center of Science and Education, 2015)
Oil and gas industry is a main revenue generation for Iran, and thousands of employees are involved in various oil and gas fields. From numerous health hazards which commonly occur in the industry one of them is psychosocial hazards. Studies confirmed a crucial step to control and understanding workplace psychosocial risk factors is developing and monitoring of policies, rules, and plans to promote health at work. This research conducted in an Iranian oil and gas company in Tehran in the period of 2011 and 2012. 248 participants were randomly selected and assigned in the study. Two questionnaires HSE and SCAT used in order to assess workplace psychosocial risks and attitude of personnel to safety climate. The result of HSE scores revealed relationships and role sub-scales in psychosocial risks were in abysmal situation. Personnel’s attitude to safety climate at the organization displayed communication, priority of safety, and involvement were at the level of “dissatisfied”. Also there was a medium positive correlation between work environment and managers’ support, relationships and change p<0.01. These findings show that safety climate factors namely communication, work environment, supportive environment, inversely affects workplace psychosocial risks. Overall, the outcomes supported the possibility that personnel attitudes to safety climate at company were predictive of higher psychosocial risks. Progress in safety climate and the psychosocial aspects of safety climate may diminish the experience psychosocial risks. Development of policies and procedures with aim of reduce psychosocial risks should be considered in Iran.